Molecular typing of classical swine fever viruses from field outbreaks in Southern India - RATHNAPRABA, S; KUMANAN, K; VIJAYARANI, K; PALANISAMMI, M; GUNASEELAN, L (The Indian Journal of Animal Sciences, 2014)
Classical swine fever (CSF) has serious economic implications and laboratory confirmation is important in early diagnosis. The present study evaluated the ability of the RT-PCR for the detection of CSFV in Southern India. So far the available information on molecular characterization of CSFV isolates from Southern states of India is limited. Hence the outbreaks occurred during 2009–2011 were studied. The outbreaks were confirmed by virus isolation and molecular detection methods employing reverse transcriptase nested PCR (RT-nPCR) targeting CSFV specific 5’UTR. Molecular detection of swine fever suspected samples (84) targeting 5’UTR resulted in 63% positivity. Virus isolation was done in PK15 cell line from 4 positive tissue samples, after 5 blind passages and the virus multiplication in cell culture system, it was checked on fifth day post infection by indirect immnunofluoroscent antibody technique (FAT). After confirming the isolates by PCR targeting CSFV specific 5’UTR the isolates were genotyped based on the 150 nt of 5’UTR inner nested region, which revealed that the 3 isolates belonged to group 1 including 1.1 and 1.2 subgroup and 1 isolate in 2.2 subgroup suggesting the circulation of group 1and 2 viruses in this region.